Correlates of correctional officer job stress: The impact of organizational structure - Lambert, Eric G. (American journal of criminal justice, 2006)
Corrections can be a very stressful occupation, producing many negative outcomes for employees. These outcomes, both mental and physical, not only affect the employee, but the entire organization. A large body of literature has focused on identifying correlates of correctional staff job stress; yet, not all of the possible correlates have been studied. One area that has received little, if any, attention is the impact of the organizational structure on correctional job stress. Organizational structure includes issues of centralization, instrumental communication, integration, and organizational justice. The results of multivariate analysis indicate that instrumental communication and procedural justice have a direct effect on correctional staff job stress.